Empowering English Teachers through Semiotic-Based Textbook Cover Design Training: A Community Service Program at SMA PGRI 1 Denpasar - Swarniti, Ni Wayan; Pusparini, Ni Made Dwi Utari; Wirasa, Komang Satria; Putri, Anak Agung Inten Meipiani; Dewi, Ni Luh Komang Ayu Sinta; Papa, Ignasius Adi (Civiliza Publishing, 2025)
This community service program aimed to enhance the pedagogical and creative competencies of English teachers at SMA PGRI 1 Denpasar through a workshop titled “Designing English Textbook Covers Based on a Semiotic Analysis Approach.” The program was divided into three phases: pre-activity, implementation, and post-activity. Initial needs assessment identified teachers’ familiarity with semiotics and visual design. The workshop provided both theoretical insights into visual semiotics and practical training using Canva to create textbook covers that reflect semiotic principles. Post-activity evaluation included post-tests, feedback forms, and continued mentoring via WhatsApp groups. The results showed significant improvement in participants’ ability to integrate symbols and signs meaningfully into cover designs, enhancing their instructional media skills. This program underscores the importance of interdisciplinary collaboration between linguists and educators in fostering media literacy and creative teaching. It serves as a model for similar initiatives in other schools and contributes to academic discourse on the application of semiotics in educational contexts.